2007
DOI: 10.1016/j.canlet.2007.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin induces angiogenesis and neuroblastoma growth

Abstract: Gastrin-releasing peptide (GRP), the mammalian equivalent of bombesin (BBS), is a trophic factor for highly vascular neuroblastomas; its mechanisms of action in vivo are unknown. We sought to determine the effects of BBS on the growth of neuroblastoma xenografts and on angiogenesis. BBS significantly increased the growth of SK-N-SH and BE(2)-C human neuroblastomas; tumors demonstrated increased expression of angiogenic markers, PECAM-1 and VEGF, as well as phosphorylated (p)-Akt levels. RC-3095, a BBS/GRP anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 29 publications
3
79
0
Order By: Relevance
“…GRP has been reported to stimulate pro-angiogenic gene expression as well as the expression of various angiogenic markers including platelet-endothelial cell adhesion molecule (PECAM-1), vascular endothelial growth factor (VEGF) and phosphorylated-Akt levels (Kang et al 2007). Moreover, GRP or GRPR silencing has been reported to significantly suppress tumor progression and vascularization (Cornelio et al 2007).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…GRP has been reported to stimulate pro-angiogenic gene expression as well as the expression of various angiogenic markers including platelet-endothelial cell adhesion molecule (PECAM-1), vascular endothelial growth factor (VEGF) and phosphorylated-Akt levels (Kang et al 2007). Moreover, GRP or GRPR silencing has been reported to significantly suppress tumor progression and vascularization (Cornelio et al 2007).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…By activating its receptors (GRPR) located on both tumor and endothelial cells, GRP is also a direct angiogenic factor as shown by in vitro and in vivo angiogenic assays (Martinez et al, 2005). In addition, GRP is able to contribute indirectly to tumor angiogenesis by augmenting expression of pro-angiogenic factors such as IL-8 and VEGF (Kang et al, 2007;. The GRP antagonist, 77427, markedly inhibits endothelial cell cord formation in vitro and inhibits angiogenesis in vivo (Levine et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Gastrin-releasing peptide is known to stimulate pro-angiogenic gene expression as well as the expression of various angiogenic markers such as vascular endothelial growth factor (Kang et al, 2007). In addition, it has been shown that GRP or GRPR silencing significantly suppress tumor progression and vascularization (Cornelio et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…High titers of GRPspecific antibodies could neutralize elevated levels of the GRP Studies have demonstrated that GRP could contribute to the increased metastatic potential of cancers through the stimulation of proangiogenic gene expression. GRP has been reported to stimulate GPRR-induced NF-B activation and upregulation of interleukin-8 gene expression (20) as well as the expression of various angiogenic markers, including PECAM-1 and VEGF, and to increase phosphorylated Akt levels (14). To our knowledge, our study is the first to demonstrate that immune responses induced by the pCR3.1-VS-HSP65-TP-GRP6-M2 anti-GRP vaccine significantly reduced tumor-associated angiogenesis and vascularization of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The GRP receptor (GRPR) is expressed aberrantly in various cancer cells (23), and GRP binding appears to activate multiple cellular signaling pathways, resulting in cellular proliferation and tumor formation (2,8). Moreover, bombesin-like peptide (BLP) family members are involved in many steps of tumor progression, including angiogenesis (9,14,20) and distant metastasis (19,22), resulting in increased aggressiveness and poorer prognosis of tumors.…”
mentioning
confidence: 99%